Intelligent Systems and Applications Proceedings of the 2018 Intelligent Systems Conference (IntelliSys) Volume 2 - Arai, Kohei; Kapoor, Supriya; Bhatia, Rahul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Gathering the Proceedings of the 2018 Intelligent Systems Conference (IntelliSys 2018), this book offers a remarkable collection of chapters covering a wide range of topics in intelligent systems and computing, and their real-world applications. The Conference attracted a total of 568 submissions from pioneering researchers, scientists, industrial engineers, and students from all around the world. These submissions underwent a double-blind peer review process, after which 194 (including 13 poster papers) were selected to be included in these proceedings. As intelligent systems continue to replace and sometimes outperform human intelligence in decision-making processes, they have made it possible to tackle many problems more effectively. This branching out of computational intelligence in several directions, and the use of intelligent systems in everyday applications, have created the need for such an international conference, which serves as a venue for reporting on cutting-edge innovations and developments. This book collects both theory and application-based chapters on all aspects of artificial intelligence, from classical to intelligent scope. Readers are sure to find the book both interesting and valuable, as it presents state-of-the-art intelligent methods and techniques for solving real-world problems, along with a vision of future research directions.
A Query Inversion Technique for Detection of Unexpected Values in Relational Databases -- Solar Radiation Time Series Analytics based on Hadoop Integrated Programming Language Environment (RHIPE) -- Performance Modeling and Analysis of the IEEE 802.11 EDCAF for VANETs -- Towards Road Safety: A Social Perception -- Evacuee Pre-Needs Assessment using Decision Tree Algorithm of MDRRMC-Daraga Records -- Inter-Cell Interference Coordination in LTE Self Organizing Network -- CIRA: An Architecture for Building Configurable Immersive Smart-Rooms -- CIRA: An Architecture for Building Configurable Immersive Smart-Rooms -- Design and Implementation of Modular IoT Platform for Home Monitoring -- The Intelligent System Design for Eliminating Blind Spots of PTZ Controlled CCTV with Raspberry Pi and Multiple Pi Cameras -- An Agent-based Modelling Framework for Driving Policy Learning in Connected and Autonomous Vehicles -- Compressive Sensing based ECG Biometric System -- Analytics in the Industrial Internet ofThings -- Design of a Network Sensing System based on Android Platform -- An Open Source Software Architecture for Smart Buildings -- Event Localization based on Direction of Arrival using Quasi Random Deployment in Internet of Things -- Traffic Surveillance for Smart City in Internet of Things Environment -- Towards Energy-Efficient RF-Enabled Sensor Networks in Internet of Things -- Big Data Channel Awareness in Cooperative D2D Wireless Fusion Networks in IoT -- A Multi-Tiers AI and IoT Architecture -- Petri Nets and Machines of Things that Flow -- Watch IT Version-II: An Assistive Device for Hearing and Speaking Impaired -- Bivariate Markov Model based Analysis of ECG for Accurate Identification and Classification of Premature Heartbeats and Irregular Beat-Patterns -- Enhancing Efficiency of Ejection Fraction Calculation in the Left Ventricle -- Application of Clustering Technique with Kohonen Self-Organizing Maps for the Epidemiological Analysis of Leprosy -- Near Real-Time Data Labeling usinga Depth Sensor for EMG based Prosthetic Arms -- U-ISLES: Ischemic Stroke Lesion Segmentation using U-Net -- A Novel Approach using Voting from ECG Leads to Detect Myocardial Infarction -- A Multi-Objective Pareto-Optimal Wrapper based Framework for Cancer-Related Gene Selection -- An Efficient Compressive Sensing Method for Connected Health Applications -- Can LANA CITS Support Learning in Autistic Children? A Case Study Evaluation -- Framework to Predict and Identify Wandering Behavior in Individuals with Alzheimer‟s using Physiological and Kinect Sensors -- Semantic Modelling of Smart Healthcare Data -- Framework to Predict Bipolar Episodes -- Functional Connectivity Evaluation for Infant EEG Signals based on Artificial Neural Network -- Classification of Cardiotocography Signals using Machine Learning -- Face Symmetry Analysis using a Unified Multi-task CNN for Medical Applications -- EVE: A Combined Physical-Digital Interface for Insomnia Sleep Diary -- Edge Computing for Low Delay to Cache andTransfer Electronic Medical Records -- Digital Exchange Communication System for Children and Youths with Autism -- Machine Learning Infused Preventive Healthcare for High-Risk Outpatient Elderly -- Data Domains Modeling Situationally Determined Evaluation.
Keywords: Computational intelligence; Control engineering; Robotics; Automation; Artificial intelligence; Computational Intelligence; Control, Robotics, Automation; Artificial Intelligence